A study of T1 relaxation time as a measure of liver fibrosis and the influence of confounding histological factors. (24th April 2015) - Hoad, Caroline L.; Palaniyappan, Naaventhan; Kaye, Philip; Chernova, Yulia; James, Martin W.; Costigan, Carolyn; Austin, Andrew; Marciani, Luca; Gowland, Penny A.; Guha, Indra N.; Francis, Susan T.; Aithal, Guruprasad P.
<x xml:space="preserve">Abstract</x> Liver biopsy is the standard test for the assessment of fibrosis in liver tissue of patients with chronic liver disease. Recent studies have used a non‐invasive measure of T1 relaxation time to estimate the degree of fibrosis in a single slice of the liver. Here, we extend this work to measure T1 of the whole liver and investigate the effects of additional histological factors such as steatosis, inflammation and iron accumulation on the relationship between liver T1 and fibrosis. We prospectively enrolled patients who had previously undergone liver biopsy to have MR scans. A non‐breath‐holding, fast scanning protocol was used to acquire MR relaxation time data (T1 and T2*), and blood serum was used to determine the enhanced liver fibrosis (ELF) score. Areas under the receiver operator curves (AUROCs) for T1 to detect advanced fibrosis and cirrhosis were derived in a training cohort and then validated in a second cohort. Combining the cohorts, the influence of various histology factors on liver T1 relaxation time was investigated. The AUROCs (95% confidence interval (CI)) for detecting advanced fibrosis (F ≥ 3) and cirrhosis (F = 4) for the training cohort were 0.81 (0.65–0.96) and 0.92 (0.81–1.0) respectively (p < 0.01). Inflammation and iron accumulation were shown to significantly alter T1 in opposing directions in the absence of advanced fibrosis; inflammation increasing T1 and iron decreasing T1. A decision tree model was developed to allow the assessment of early liver disease based on relaxation times and ELF, and to screen for the need for biopsy. T1 relaxation time increases with advanced fibrosis in liver patients, but is also influenced by iron accumulation and inflammation. Together with ELF, relaxation time measures provide a marker to stratify patients with suspected liver disease for biopsy. Copyright © 2015 John Wiley & Sons, Ltd.